CHARACTER, PSYCHOANALYTIC IDENTIFICATION, AND NUMERICAL IDENTITY - Braddock, Louise (Ratio (Oxford), 2012)
Identification figures prominently in moral psychological explanations. I argue that in identification the subject has an ‘identity‐thought’, which is a thought about her numerical identity with the figure she identifies with. In Freud's psychoanalytic psychology character is founded on unconscious identification with parental figures. Moral philosophers have drawn on psychoanalysis to explain how undesirable or disadvantageous character dispositions are resistant to insight through being unconscious. According to Richard Wollheim's analysis of Freud's theory, identification is the subject's disposition to imagine, unconsciously, her bodily merging with the figure she identifies with. I argue that this explanation of identification is not adequate. Human character is held to be capable of change when self‐reflection brings unconscious identifications to conscious self‐knowledge. I argue that for self‐knowledge these identifications must be an intelligible part of the subject's self‐conception, and that Wollheim's ‘merging phantasy’ is not intelligible to the subject in this way. By contrast, the subject's thought that she is numerically identical to the figure she identifies with does provide an intelligible starting‐point for reflecting on this identification. This psychoanalytic account provides a clear conception of identification with which to investigate puzzle cases in the moral psychology of character.